The Fragility of Church Unity and Diversity in the Metaphor of Jigsaw Puzzle - Andri Fransiskus Gultom (Actual Insight, 2025)
Harls E.R. Siahaan and Johannis Siahaya offer a descriptive understanding in overcoming church diversity through the jigsaw puzzle metaphor. Metaphor, for them, becomes the basic element that forms a picture of church as a perfect and complete blueprint. This article focuses on substantively critiquing the articles of both authors as a form of dialectical continuity that unity and diversity have a broader horizon than just the jigsaw puzzle metaphor. This research uses a qualitative method with the following steps: verstehen (in-depth reading of the text), comparison, and interpretation. This research found that: (1) the explanation of the dialectical model is not explicitly elaborated, both semantically and in the paradigm of ontology; (2) the Jigsaw Puzzle metaphor becomes fragile because it is not based on the dialectical history of thought; (3) the neologisms such as: meroecclesia, somaecclesia, are not based on the history of thought and tend to favor Pentacostalism; (4) the discourse on hospitality is incommensurable with the jigsaw puzzle metaphor. This article reveals the differentiation between unity and diversity.